Primary Students' Errors in Solving Mathematical Literacy Problems Based on Newman Analysis - Mubarokah, Aysha Amini Laylatim; Amir, Mohammad Faizal (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Successfully solving mathematical literacy problems by primary students is essential to prepare an earlier generation to deal with various problems in life contexts and have a positive motivation towards mathematics. Previous empirical evidence shows that primary students are still solving mathematical literacy problems with various incorrect strategies and various levels of errors. Meanwhile, Newman Errors Analysis (NEA) can be used to analyze the forms of primary students' errors in solving problems. This research aims to analyze the forms of primary students' errors in solving mathematical literacy problems using NEA. This research applied a qualitative method, with subjects consisting of 35 fifth-grade primary students. Data was collected using tests, interviews, and documentation. Data analysis techniques regarding primary students' errors were carried out through three stages: data reduction, data presentation, and conclusion drawing. The forms of errors are emphasized in NEA categories, namely reading, comprehension, transformation, process skills, and encoding. The results showed that primary students made all forms of Newman errors in solving mathematical literacy problems. The highest form of error is comprehension errors, while the lowest is process skill. The research results suggest that primary students need to be familiar with numeracy learning, emphasizing meaningful comprehension to avoid errors in solving mathematical literacy problems.